الأنثروبولوجيا العربية في ميزان الثنائية - جفال, نورالدين (Changement Social; No 4 (2018): revue change social, 2018)
ربما يتبادر الى الاذهان من حين الى اخر فكرة وجود او عدم جود اصلا لما يسمى الانثروبولوجيا العربية, أو بالأحرى كل ما هو مكتوب باللغة العربية من طرف باحثين انثروبولوجين عرب هو عربي بحث، أو اعادة ديباجة افكار غربية بأقلام عربية دون الحياد عن المناهج والأدوات التحليل العلمي الغربي، ام هي ارهاصات متجدرة من لبنات افكار دارسين عرب في هذا الميدان, تنتظر الدفع لمستقبل علمي زاهر مستقل جذريا عن جوهر الفكر الغربي الانثروبولوجي باعتبار ان الانثربولوجي العربي ادرى من غيره بالإنسان العربي، وإن كان و لابد فسيرورة إلى الامام حتمية للإنتاج انثروبولوجيا مستقبلية, بغض النظر عن جوهرها أكان مقولبا غربيا أو عربيا، ربما يتوقف هذا على درجة كفاءة الباحثين الانثروبولوجين العرب ومدى استقلاليتهم الفكرية عن الفكر الانثروبولوجي الغربي في جوهره عموما والصنمية العلمية خصوصا، ففي هذه الورقة نحاول ان نعالج بطريقة مقاربتية نظرية وتوصيفية في آن واحد اشكالية المطروحة في عنوان هذه المداخلة. time to time the idea of the existence or non-existence of out of the so-called anthropology Arab or rather all that is written in Arabic anthropologist researchers party Arab is an Arab search or repreamble to Western ideas of Arab pens without deviate from the curriculum and tools Western scientific analysis or are harbingers rooted from the brainchild of students Arabs in this field Abstract : May be that comes to mind from time to time the idea of the existence or non-existence of out of the so-called anthropology Arab or rather all that is written in Arabic anthropologist researchers party Arab is an Arab search or repreamble to Western ideas of Arab pens without deviate from the curriculum and tools Western scientific analysis or are harbingers rooted from the brainchild of students Arabs in this field waiting to pay for the future of scientific independent radically from the essence of Western thought anthropologist considering that the Arab Anthropology wonder other Arab human beings, though, and forever forward the inevitable production of future anthropology regardless of the essence Western or Arab, this probably depends on the degree of efficiency of researchers anthropologist Arabs and their intellectual independence for Anthropology of Western thought in general, scientific and idolatry especially essence, in this paper we are trying to address approach way theory and descriptive at the same time problematic posed in the title of this intervention.